Penguatan Kelembagaan Bumdes Sejahtera Desa Darunu Kecamatan Wori, Kabupaten Minahasa Utara Melalui Penyusunan Awal Laporan Keuangan - Heidy Pesik; Johanes Herebert Tene; Valensiana; Julita Waney; David Kalao (Syntax Corporation Indonesia, 2024)
Village-Owned Enterprises or BUMDes Sejahtera Darunu Village, located in Wori District, North Minahasa Regency, still faces various obstacles in optimal financial management. The main problems include limited knowledge related to the management of cash inflows and outflows as well as limited understanding of human resources (HR) of village officials in preparing financial reports. In addition, this BUMDes does not yet have a basic financial report as a guideline for financial operations. Thus, this research aims to strengthen the BUMDes Sejahtera institution through the preparation of standardized initial financial statements. The research used descriptive qualitative methods by collecting data through interviews and direct observation. The participatory and applied nature of the research also helped researchers play an active role in providing training and mentoring for BUMDes administrators. The data obtained was then analyzed in three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that this institutional strengthening initiative had a positive impact on the initial understanding of BUMDes management in preparing financial statements. The program successfully produced several important financial reports, such as the 2023 Balance Sheet, 2023 Profit and Loss Statement, and 2024 Current Profit and Loss Statement. Hopefully, this institutional strengthening will be implemented sustainably to advance BUMDes Sejahtera and provide optimal benefits for the progress of Darunu Village.